2012
DOI: 10.1590/s1516-89132012000400007
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of lipid profile and oxidative stress in STZ-induced rats treated with antioxidant vitamin

Abstract: The present study investigated the effect of supplementation of vitamin E on streptozotocin (STZ)-induced diabetic rats by measuring blood glucose, changes in body weight, food and water intake, lipid profile, serum urea and creatinine level, and antioxidant enzyme activity. Male Wistar rats were divided into four groups: control rats (GI); rats receiving vitamin E (GII); STZ-induced diabetic rats (GIII) and STZ-induced diabetic rats treated with vitamin E (GIV). Vitamin E reduced (p<0.05) blood glucose and ur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
23
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(35 citation statements)
references
References 54 publications
11
23
0
1
Order By: Relevance
“…Further, the serum urea levels were significantly increased after 3 months of diabetes induction, but there is no change in creatinine levels which is in contrast to the previous report where the urea and creatinine levels were found to be higher after 1 month of diabetes induction. [22] These findings confirm the induction of diabetes mellitus in the STZ-induced rats.…”
Section: Discussionsupporting
confidence: 66%
“…Further, the serum urea levels were significantly increased after 3 months of diabetes induction, but there is no change in creatinine levels which is in contrast to the previous report where the urea and creatinine levels were found to be higher after 1 month of diabetes induction. [22] These findings confirm the induction of diabetes mellitus in the STZ-induced rats.…”
Section: Discussionsupporting
confidence: 66%
“…In diabetes, reduced body weight is due to loss of proteins and lipid as a result of proteolysis and lipolysis (Hebert & Nair, 2010). The body weight in diabetic rats was significantly decreased compared to normal rat, as shown in previous study (Almeida et al, 2012). The diabetic rat group showed a consistent higher blood glucose level as expected (Cheng et al, 2013), while aqueous extract of H. sabdariffa (HSE) was shown to successfully reduce the blood glucose level significantly probably due to polyphenols are well known as hypoglycaemic agents (Ojulari et al, 2014; Rosemary et al, 2014).…”
Section: Effects Of Hpe On Body Weight and Blood Glucosesupporting
confidence: 68%
“…The result of the present study also indicates that the d-δ-TRF treatment enhances protein synthesis in treated groups and its level is lower in DC, which is in agreement with another study [28] which found that diabetic rats showed lower serum total protein level, and when treated with vitamin E, its level improves significantly.…”
Section: Discussionsupporting
confidence: 93%